14‐2: Invited Paper: OLED Display Incorporating an Organic Image Sensor. Issue 1 (25th September 2020) - Niikura, Yasuhiro; Hatsumi, Ryo; Kamada, Taisuke; Yamashita, Akio; Watanabe, Kazunori; Kawashima, Susumu; Yamauchi, Ryo; Katayama, Masahiro; Adachi, Hiroki; Kusunoki, Koji; Kubota, Daisuke; Eguchi, Shingo; et al.
Abstract : We fabricated a prototype display that incorporates an organic image sensor in the same pixel as OLEDs through side‐by‐side patterning. The display enables fingerprint image capturing and scanning at any location on the entire display region. We fabricated a flexible OLED display with the aforementioned structure.